Effective total synthesis of schaftoside. (2nd July 2021) - Shang, Chengxiang; Zhao, Chuanfang; Nie, Pengpeng; Liu, Jun; Du, Yuguo
Abstract: A short and scalable approach toward the total synthesis of schaftoside, a naturally occurring bioactive C -glycosylflavone, has been developed from readily available (±)-naringenin. The highlights of this work are double Lewis acid promoted O→C rearrangement to form C-glycoside, oxidative dehydrogenation to construct flavone ring, and easy operational process to make the target product in multigram-scale. Graphical abstract: Image 1